An Abdominal Wall Endometriosis at Jimma University Medical Centre, Ethiopia: A Case Report: Abdominal Wall Endometriosis - Debela, Dejene Tolossa; Hussein, Kelil; Girma, Wubishet; Disasa, Fanta Asefa; Mudasir, Tofik; Zerihun, Filagot (Ethiopian Journal of Reproductive Health, 2026)
Background: Abdominal wall endometriosis is a rare condition, often occurring as a complication following gynecologic surgery, especially caesarean sections. Its diagnosis is frequently delayed due to non-specific symptoms and a wide range of differential diagnoses. Case Description: We report A 25-year-old woman, para 1 by caesarean section, presented with cyclic left lower abdominal pain and swelling, worsening during menstruation. Physical examination revealed a firm, nontender mass near the caesarean scar. Imaging studies including ultrasound and color Doppler identified a hypoechoic lesion in the rectus abdominis muscle with internal vascularity. Fine needle aspiration cytology supported a diagnosis of endometriosis. Intervention and Outcome: Surgical excision under spinal anaesthesia was performed in complete removal of the lesion, with no postoperative complications. The patient remained symptom-free at six-month follow-up. Conclusion: This case highlights the importance of considering abdominal wall endometriosis in women with cyclical pain and prior uterine surgery. Imaging and histopathology are key to diagnosis, while complete surgical excision remains the definitive treatment.